Coping strategy among Parents of children with thalassemia in India - Bala, Jyoti (Journal of Neonatal Surgery, 2025)
Background: In a country like India, where over 40 million people carry the gene for thalassemia major and over 10,000 children are born each year with the severe form of thalassemia, 80-90% fail to survive beyond the age of ten. Most of thalassaemic children with thalassemia if not treated properly, have the difficulty in daily activities. Yet, there is a cure for thalassemia. Bone marrow transplantation and stem cell transplantation is very costly which is beyond the reach for majority of affected families, even if they have a donor in the family. Long term supportive care with transfusion and iron chelation is beyond the means of most families. Hence Families with thalassemic children often experience difficulties in adaptation to the illness. Objective of the study were to assess and compare the coping strategy of parents in experimental and control group regarding care of children with thalassemia; and to determine the association of coping strategy of parents with selected variables. Methods: A quasi-experimental study following pretest post-test research design was conducted among 107 parents and their thalassaemic children (54 in experimental and 53 in control group) in two randomly selected hospitals in Delhi. Structured Teaching Program (STP) comprised of two programme i.e. STP- I includes the items related to knowledge whereas STP-II focused on the psychological problem of parents. Pretest and post-test coping strategy of parents (day 30 and day 60) were assessed using a valid and reliable coping checklist. Results: The mean posttest coping strategy scores of parents in experimental group was higher than control group as on day 60 (E=50.61, C=47.88). The computed t(106)= 2.14 on day 60 was statistically significant at 0.05 level of significance. The area wise analysis showed effectiveness of coping in the area of planful problem solving, seeking social support, self control. There was no significant association found between the post-test coping strategy score of parents with selected variables except the family history of thalassemia. Conclusion: Structured teaching Program was effective in improving the adaptive coping strategy among parents of Children with Thalassemia but unfortunately no literature or study was found to explain these finding.